Long-term Growth Hormone Associated with High Risk of Acute Kidney Damage - Ahmed Jamal Chaudhary, Wasil Khan, Aijaz Zeeshan Khan Chachar, Waqif Shehzad, Muhammad Khan Malik, Salman Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Prolonged exposure to growth hormone (GH) therapy produces several alterations in body metabolism as well as changes within organs. The kidney effects of growth hormone expose ongoing debate for patients who already have medical issues. The research evaluates how long-term administration of growth hormone therapy (GHT) affects the probability of developing acute kidney damage. Objective: To assess the long-term impact of growth hormone therapy on kidney function, particularly focusing on the incidence of acute kidney damage (AKI) among individuals undergoing prolonged GH treatment. Methodology: This prospective cohort study was conducted at Lahore Medical and Dental College during May 2022 to January 2023. A total of 175 patients were added in the study. Data was collected from a cohort of 175 patients undergoing long-term growth hormone therapy for more than 1 years. Participants underwent baseline assessments to record demographic data, including age, gender, body mass index (BMI), and medical history (such as hypertension, diabetes, obesity, and smoking/alcohol consumption). Results: A total of 175 patients were added in the study with a mean age of 45.6 ± 8.2 years, with 65% male and 35% female participants. The average body mass index (BMI) was 27.4 ± 4.5 kg/m². Pre-existing conditions included 25.7% with hypertension, 16.0% with diabetes, and 17.1% with obesity. Additionally, 24.0% of participants were smokers, and 11.4% consumed alcohol. Hypertension had the highest odds ratio (OR = 3.2, 95% CI: 2.0 - 4.8, p < 0.001), indicating a strong association with AKI. Diabetes also showed a significant risk (OR = 2.8, 95% CI: 1.7 - 4.5, p = 0.002), followed by obesity (OR = 2.1, 95% CI: 1.1 - 3.9, p = 0.03). Conclusion: Long-term growth hormone therapy may increase the risk of acute kidney damage, particularly in individuals with pre-existing renal risk factors. Careful monitoring of kidney function in patients undergoing long-term GH treatment is recommended to mitigate the risk of AKI. Keywords: Growth Hormone, Acute Kidney Damage, GH treatment